Mycobacterium - Research and Development 2018
DOI: 10.5772/intechopen.73546
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium as Polycyclic Aromatic Hydrocarbons (PAHs) Degrader

Abstract: The genus Mycobacterium has the ability to degrade various environmental pollutants including polycyclic aromatic hydrocarbons (PAHs). Mycobacterium has an ability to withstand adverse environmental conditions and it has been considered for future bioremediation applications for the removal of PAH contaminants from crude oil-polluted sites. The degradation of PAHs using a cost-effective laboratory microcosm system was discussed. The various conditions such as environmental habitat, degradation behavior, enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
7
0
2
Order By: Relevance
“…Several Mycobacterium strains were human pathogenic species. However, some species, such Mycobacterium austroafricanum and Mycobacterium sp ., have been identified to have the ability to degrade aromatic hydrocarbons [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several Mycobacterium strains were human pathogenic species. However, some species, such Mycobacterium austroafricanum and Mycobacterium sp ., have been identified to have the ability to degrade aromatic hydrocarbons [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…synthetized dioxygenases or monooxygenases which was able to degrade PAHs. It is known that bacterial dioxygenases can catalyze the incorporation of both atoms of oxygen and two electrons from NADH to form cisdihydrodiol, while monooxygenases can hydrolyze PAHs into trans-dihydrodiols and this activity is slower than dioxygenases (Dudhagara and Dave 2018). In addition, some researchers suggested that the particular cell wall layer of mycobacteria, such as mycolic acids, is also important for the degradation of hydrophobic compounds (Zeng et al 2010).…”
Section: Taxonomic Composition Analysismentioning
confidence: 99%
“…Nowadays, in order to eliminate PAHs from the environment by bioremediation, many PAHdegradation microorganisms have been isolated. Most of these bacteria belong to the genera Pseudomonas, Rhodococcus, Paenibacillus, Acinetobacter, Bacillus and Mycobacterium [15,16,2,17]. The aerobic and anaerobic bacteria species have been reported extensively in the literature for the degradation of low molecular weight (LMW) and high molecular weight (HMW) PAHs through pure cultures, consortia and mixed bacterial culture approaches (Patel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%